Policy Innovation Adoption Across the Diffusion Life Course. - Mallinson, Daniel J. (Policy Studies Journal, 2021)
This study develops and tests a theory of the diffusion life course using a dataset of 566 policies adopted between 1960 and 2016. Previous small‐N studies found differences between leaders and laggards, but broader innovation theory points to five stages of adoption: innovation, early adoption, early majority, late majority, and laggard. This study demonstrates that predictors of policy adoption change throughout the diffusion life course. Neighbor adoptions matter early in the life course but are supplanted by the consistent effect of ideological learning across all stages. The results confirm that less professionalized states tend to adopt later. Finally, state wealth and population size are increasingly important as policies spread. These results have implications for our understanding of when and why states adopt policy innovations. They also illustrate the substantial opportunity for political science and public policy researchers to draw from broader theories.